From Culture to Performance: Unpacking the Role of Job Stress in the Modern Coffee Workplace at Surabaya - Antonius Yuniarto; Garry Nowel (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study investigates how organizational culture and job characteristics influence job performance, mediated by job stress, among employees of Ame Coffee. Data were collected from 115 respondents across Ame Coffee outlets using purposive sampling, with questionnaires distributed via Google Forms. Demographic variables such as gender, age, education, and work tenure were analyzed. Partial Least Squares (PLS) analysis in PLS 4.0 revealed that organizational culture significantly affects job stress and, indirectly, job performance. However, job stress itself does not directly impact performance. Surprisingly, job characteristics showed no significant influence on either job stress or performance when mediated by stress. These findings underscore the critical role of organizational culture in shaping workplace dynamics while suggesting the need for further research on job design and employee well-being.